Desarrollo de las redes sociales como herramienta de marketing. Estado de la cuestión hasta 2015 (2015)
This article describes why social media become an almostessential element in today’s business management. In reachingthis conclusion a number of qualitative and quantitativetechniques were used. It highlights the advantages and featuresof the implementation of a Social Media Plan in order to argueand reason the benefits that a proper management of a strategyin social media provide to an organization.